Efek Terapi Sardinella longiceps Terhadap Tinggi Tulang Kortikal Mandibula Tikus Model Periodontitis - Nur Octavia; Widyastuti; Dianty Saptaswari; Dian Widya Damaiyanti (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2019)
Background: Periodontitis begins with accumulation of pathogenic plaque containing bacteria and toxins. Subgingival bacteria found in chronic periodontitis are one of them is Porphorymonas gingivalis. Porphyromonas gingivalis bacteria causes progressive damage to the supporting tissues of the teeth, especially the alveolar bone. Alternative medicine that can be used is with herbal ingredients, namely Sardinella longiceps. Sardinella longiceps contains omega 3 (DHA and EPA) which inhibits proinflammatory cytokines thereby accelerating the process of bone regeneration. Objective: This study aims to determine whether the administration of gel (Sardinella longiceps) affects the height of the cortical bone of the mandibular periodontitis-induced rat Porphyromonas gingivalis.Research Methods: 25 male Wistar rats were divided into 5 groups. P0 is the normal group that is not treated. P + is a group induced by Porphyromonas gingivalis. P1, P2, P3 are the groups induced by Porphyromonas gingivalis and given Sardinella longiceps gel with concentrations of 10%, 20%, 40% respectively. On the 55th day all model mice were treated and mandibular cortical bone height was measured using a digital caliper in the interdental region of the 1st molar and left lingual molars from the apex of the alveolar bone to the mandibular base. The data obtained were analyzed by one way ANOVA followed by LSD (p = 0.05). Results: Statistical tests showed the mean height of mandibular cortical bone was P0 (5.21 ± 0.21), P + (4.67 ± 0.25), P1 (5.12 ± 0.14), P2 (5.51 ± 0.12), and P3 (5.88 ± 0.13). There was a significant difference (p <0.05) between treatment groups and positive control groups (p <0.05). Conclusion: Sardinella longiceps affects the height of the cortical bone of the periodontitis rats model induced by Porphyromonas gingivalis bacteria. The most effective in the group of sardinella longiceps gel with a concentration of 40%.